Pre-season training process improvement for success in junior middle-distance races - Mosin, I. V.; Esaulov, M. N.; Mosina, I. N. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2017)
Objective of the study was to improve the precompetitive training process of 800 m racers at the sport excellence stage and to find, among other things, the optimal pre-season training (PST) cycle time. We believe that the special training load profiling models applicable at the PCT stage of the 18-19 years-old 800 m racers will be duly customized to the adaptive capabilities of the junior athletes with consideration for the cumulative effects of the competitive periods. The PCT process design we offered was modified for the junior athletes so as to split it up into three biweekly meso-cycles with weekly rehabilitation micro-cycles finalized by special combined tests. The study found the PCT training workloads in the Study Group being well customized for the athletes` competitive adaptation abilities to facilitate their successful competitive performance in a series of events with stable competitive progress being assured. The Reference Group workloads were found inadequate to secure good competitive performance and, therefore, the desired competitive success rates were not achieved.